2007
DOI: 10.2214/ajr.07.2165
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Breast Biopsy: Comparison of Histologic Underestimation Rates with 11- and 9-Gauge Vacuum-Assisted Breast Biopsy

Abstract: There was no statistically significant difference between 11-gauge biopsy and 9-gauge biopsy in underestimation of atypical ductal hyperplasia and ductal carcinoma in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 28 publications
2
39
3
1
Order By: Relevance
“…The two systems used in this study differ in the size of the probe needle, with the EnCor ® using the larger (10G) needle compared to the Mammotome ® (11G). This difference in size, a single value in the Gauge scale, did not lead to superior performance as also observed by Lourenco et al [11]. Significantly better performances were observed when greater calibre differences were considered, as in the study by Venkataraman et al [12], who compared 8G vs. 11G needles.…”
Section: Discussionsupporting
confidence: 69%
“…The two systems used in this study differ in the size of the probe needle, with the EnCor ® using the larger (10G) needle compared to the Mammotome ® (11G). This difference in size, a single value in the Gauge scale, did not lead to superior performance as also observed by Lourenco et al [11]. Significantly better performances were observed when greater calibre differences were considered, as in the study by Venkataraman et al [12], who compared 8G vs. 11G needles.…”
Section: Discussionsupporting
confidence: 69%
“…Although SVAB allows more accurate histopathologic results, underestimation still occurs (7,10,18). Some investigators have found rates of underestimation ranging from 5% to 29% for DCIS at SVAB (6,9,(11)(12)(13). In this study, the underestimation rate of DCIS was 18%.…”
Section: Discussionmentioning
confidence: 50%
“…Underestimation of DCIS lesions occurs when an invasive component is found after surgery, which had been missed at the initial preoperative sampling. The underestimation rate of stereotactic 14-gauge automated core biopsy in DCIS was reported as 16%-35% (9-11), while that of SVAB was 5%-29% (6,9,(11)(12)(13).…”
Section: Resultsmentioning
confidence: 99%
“…Technical advances in percutaneous core needle biopsy, such as increasing needle diameter from 14-gauge to 11-gauge and adding a vacuum device, have allowed larger samples of tissue to be obtained (5,6), substantially improving the accuracy of diagnosis. Despite these improvements, the rate of underestimation for ADH has been reported as 10% to 26% for 11-gauge vacuum-assisted biopsy (VAB) (2,14,(21)(22)(23)(24)(25)(26)(27)(28). In this study, 11-gauge SVAB was associated with a lower rate of underestimation for ADH (20.6%), compared to USguided 14-gauge automated biopsy (41.7%) (P = 0.007).…”
Section: Discussionmentioning
confidence: 84%